Factors affecting the social gradient in children's social care. (11th January 2022) - Goldacre, Allie; Hood, Rick
Abstract: The social gradient in children's social care refers to the relationship between socio-economic status and the likelihood of a child welfare intervention. This article reports on a quantitative study of national administrative data, aiming to identify social gradients across all local authorities in England and to examine the factors affecting their relative strength. An anonymised extract of case-level information on all school-aged children involved with statutory social care services in 2018–2019 was combined with income deprivation data for 32, 837 small neighbourhoods. Poisson regression models were used to calculate how much intervention rates could be expected to rise for each 10 percent increase in neighbourhood deprivation. This produced a single number indicator of the social gradient that could be compared for different groups of children. The strongest social gradients were found for younger children, White children, children assessed with neglect and children on protection plans under the category of neglect. For children receiving statutory services the social gradient increased at every threshold of intervention. Findings suggest the shift from prevention to intervention in children's social care is exacerbating inequalities and encouraging a disproportionate focus on poorer families. Implications are discussed for reforming child welfare services in the context of widening social inequalities. Abstract : There is a significant social gradient for children's social care services, which means they disproportionately intervene with children from more deprived backgrounds. Higher social gradients were found in certain types of areas and for certain types of children. Addressing these inequalities will require a shift away from late intervention and investment in a public health approach to child welfare.